PERSEPSI KONSUMEN DAN KEPUTUSAN PEMBELIAN TERHADAP PENGGUNAAN BIO-PLASTIC (Suatu Kasus pada Kini&Nanti Kopi, Jakarta Selatan) - Febhy Anjani Poetri; Trisna Insan Noor (Universitas Galuh Ciamis, 2020)
Plastic waste has become one of the causes of environmental problems in Indonesia. The production of plastic waste that uses non-biodegradable materials every year always increases. DKI Jakarta is one of the cities with the most plastic waste production in Indonesia. Increased public awareness of the importance of environmental sustainability, marked by the emergence of the use of bio-plastic as an effort to reduce plastic waste. Based on these problems, this study aims to determine consumer perceptions and purchasing decisions on the use of bio-plastic in Kini & Nanti Coffee. This study uses quantitative research designs and survey methods using questionnaires as an aid in conducting interviews. The analysis used in this study is the validity test, reliability test, descriptive statistical analysis, factor analysis, and Spearman rank correlation analysis. The results showed that the most dominant factor influencing consumer perceptions was quality, the most dominant factor influencing purchase decisions was problem recognition and consumer perceptions significantly affected purchasing decisions.